Tourism Promotion Mechanism Based on Virtual Reality Technology for Real-life Interactive Experience - Nie, Xinxin; Pu, Jing (Informatica, 2025)
The development of the national economy has promoted the development of the tourism industry, and outdoor tourism has gradually become the main leisure and entertainment method for people during holidays. However, the current tourism promotion mechanism only considers tourist preferences, resulting in tourists receiving recommendations, and the unique features of the tourist attractions in the destination area are extremely similar to those of previous tourist areas. Therefore, based on the Visual Geometry 19 model, this study designs a residual network for feature extraction, and then uses panoramic stitching technology to construct a virtual scene of tourist attractions. The results showed that the designed residual network performed better in training and testing on the tourism map dataset, and could converge in 50 iterations. During the testing process, its accuracy could also reach around 75%. The designed tourism attraction promotion mechanism based on virtual reality technology effectively solves the problem of single tourism promotion and improves the experience of national outbound tourism.